2014
DOI: 10.1002/jip.1425
|View full text |Cite
|
Sign up to set email alerts
|

South African Serial Homicide: Offender and Victim Demographics and Crime Scene Actions

Abstract: There is an abundance of literature on serial homicide from a Western perspective that outlines operational definitions, types of offenders and how they prey upon their victims. However, currently, there is a lack of studies that compare serial homicide in different countries. The current study aims to give an overview of the demographics of serial homicide offenders and victims in South Africa and compare these to the demographics of offenders and victims from other currently available empirical studies of ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 33 publications
(78 reference statements)
1
28
0
Order By: Relevance
“…Cross‐national comparisons can help us identify the common features of serial homicide in general and the distinct features that are influenced by the country in which the homicides occur, and by so doing increase our understanding of the phenomenon both from a theoretical standpoint and in terms of the practical application of the models in the investigative process (Lafree, ). Cross‐national research enables us to explore local contextual differences in two domains: (1) tool availability and physical environment and (2) psychological factors (Salfati, Labuschagne, Horning, Sorochinski, & De Wet, ). The first domain may impact how the offender plans to commit his or her crimes and what means he or she chooses to accomplish them.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐national comparisons can help us identify the common features of serial homicide in general and the distinct features that are influenced by the country in which the homicides occur, and by so doing increase our understanding of the phenomenon both from a theoretical standpoint and in terms of the practical application of the models in the investigative process (Lafree, ). Cross‐national research enables us to explore local contextual differences in two domains: (1) tool availability and physical environment and (2) psychological factors (Salfati, Labuschagne, Horning, Sorochinski, & De Wet, ). The first domain may impact how the offender plans to commit his or her crimes and what means he or she chooses to accomplish them.…”
Section: Introductionmentioning
confidence: 99%
“…However, the per cent of Black offenders was slightly underrepresented in terms of the racial distribution of the population. Generally, racial composition of serial homicide offenders reflects that of the population where the homicide takes place (Salfati et al ., )…”
Section: Resultsmentioning
confidence: 99%
“…Salfati et al . () also found that in South Africa, some common victim groups were women seeking employment and children, but sex workers were rarely targeted. According to Egger (2002), certain members of society are deemed as having less ‘human worth’, and therefore, they are more subject to violence.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations